Event tourism as a tool for patriotic education of youth - Veres, Kateryna; Serha, Tetyana (My University, 2014)
Event tourism become in creasingly popular in recent years, which is widely regarded as a fundamentally new and certainly interesting trend in tourism. The main purpose of event tourism is visiting not places of interest, but-as also evidenced by their name - visiting events. During the event tour, tourists get a new "a reason" to visit the famous objects of tourist attraction and sometimes become a member of interesting events in the world of culture, art and sport.
Keywords: event tourism; подієвий туризм; туристична привабливість; tourist attraction; інновації (туризм); кафедра туристичного та готельного бізнесу